Antisense transcription‐dependent chromatin signature modulates sense transcript dynamics. Issue 2 (12th February 2018) - Brown, Thomas; Howe, Françoise S; Murray, Struan C; Wouters, Meredith; Lorenz, Philipp; Seward, Emily; Rata, Scott; Angel, Andrew; Mellor, Jane
Abstract: Antisense transcription is widespread in genomes. Despite large differences in gene size and architecture, we find that yeast and human genes share a unique, antisense transcription‐associated chromatin signature. We asked whether this signature is related to a biological function for antisense transcription. Using quantitative RNA‐FISH, we observed changes in sense transcript distributions in nuclei and cytoplasm as antisense transcript levels were altered. To determine the mechanistic differences underlying these distributions, we developed a mathematical framework describing transcription from initiation to transcript degradation. At GAL1, high levels of antisense transcription alter sense transcription dynamics, reducing rates of transcript production and processing, while increasing transcript stability. This relationship with transcript stability is also observed as a genome‐wide association. Establishing the antisense transcription‐associated chromatin signature through disruption of the Set3C histone deacetylase activity is sufficient to similarly change these rates even in the absence of antisense transcription. Thus, antisense transcription alters sense transcription dynamics in a chromatin‐dependent manner. Synopsis: Quantitative RNA‐FISH experiments in combination with a stochastic model of transcription reveal that antisense transcription disrupts the activity of the Set3 lysine deacetylase, thus altering the rates of sense transcript production, processing and stability. A conserved antisense transcription‐dependent chromatin architecture is identified near promoters. Antisense transcription alters sense transcription dynamics and transcript stability. Antisense transcription functions in a chromatin‐dependent manner. Increased acetylation by set3Δ mimics high antisense transcriptional dynamics. Abstract : Quantitative RNA‐FISH experiments in combination with a stochastic model of transcription reveal that antisense transcription disrupts the activity of the Set3 lysine deacetylase, thus altering the rates of sense transcript production, processing and stability.